A phase I study of pharmacokinetics of trastuzumab emtansine in Chinese patients with locally advanced inoperable or metastatic human epidermal growth factor receptor 2-positive breast cancer who have received prior trastuzumab-based therapy. Issue 44 (30th October 2020) - Ji, Dongmei; Shen, Weina; Zhang, Jian; Cao, Junning; Li, Wenhua; Lam, Lisa H.; Wu, Fan; Wang, Bei; Li, Zao; Sun, Guofang; Hu, Xichun; Chen, Shang-Chiung
Abstract: Background: Trastuzumab emtansine (T-DM1) is an antibody–drug conjugate that retains the antitumor effects of trastuzumab while also delivering the cytotoxic antimicrotubule agent, DM1, directly to tumor cells that overexpress human epidermal growth factor receptor 2. The pharmacokinetic (PK) profile of T-DM1 has been well characterized in Western, Asian, and Japanese patients; this single-center, phase I study (NCT03153163) examined the PK of T-DM1 and safety specifically in Chinese patients. Methods: Patients with locally advanced or metastatic breast cancer, previously treated with trastuzumab and a taxane, received open-label T-DM1 at 3.6 mg/kg every 3 weeks. Serum T-DM1 and total trastuzumab, and plasma DM1 were evaluated, and PK parameters were calculated using standard noncompartmental approaches. Adverse events (AEs) were assessed, and immunogenicity was evaluated by measuring antidrug antibodies to T-DM1. Results: Among 11 Chinese patients, mean (±standard deviation) PK parameters (maximum serum concentration, 77.6 ± 17.4 μg/mL; clearance 11.0 ± 2.6 mL/d/kg; terminal half-life 3.8 ± 1.0 days) were similar to those previously reported in Western and Japanese patients. One patient transiently developed antidrug antibodies, which did not appear to influence safety or PK. T-DM1 was generally well tolerated. Grade 3–4 AEs occurred in 7 patients (63.6%) and serious AEs occurred in 4 patients (36.4%). Platelet count decrease was the most common all-grade AE (10/11; 90.9%), grade 3–4 AE (5/11; 45.5%), and serious AE (3/11; 27.3%), but did not appear to be associated with any clinically significant bleeding events. Conclusions: T-DM1 PK in Chinese patients was consistent with those in global and Asian populations, supporting its use in patients with advanced human epidermal growth factor receptor 2-positive breast cancer following progression on trastuzumab and a taxane. The safety profile of T-DM1 was consistent with prior experience.